1993
DOI: 10.1161/01.atv.13.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of exercise-induced shortening of bleeding time by fish oil in familial hypercholesterolemia (type IIa).

Abstract: Fourteen patients suffering from familial hypercholesterolemia (type Ha) participated in a double-blind, placebo-controlled trial that evaluated! the effects of fish oil ethyl ester (K-85, 5.7 g/day) or a hydroxymethylglutaryl coenzyme A reductase inhibitor (lovastatin, 40 mg/day) alone or in combination on lipid metabolism and bleeding time at rest and after standardized exercise. Lovastatin treatment reduced total cholesterol (-27%), low density lipoprotein cholesterol (-37%), and triglycerides (-18%), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Nicotinic acid which may effectively reduce both TC and TG levels may have adverse effects on glucose metabolism and is often difficult to tolerate. It has previously been shown that the combination of omega-3 fatty acids and statins may effectively reduce both total cholesterol and triglycerides in patients with combined hyperlipidemia and familial hypercholesterolemia [8,36]. The present study has confirmed these observations and furthermore has shown that omega-3 fatty acids have an additive effect in lowering triglycerides, total cholesterol (borderline) and apoE when added to the statins.…”
Section: Discussionsupporting
confidence: 87%
“…Nicotinic acid which may effectively reduce both TC and TG levels may have adverse effects on glucose metabolism and is often difficult to tolerate. It has previously been shown that the combination of omega-3 fatty acids and statins may effectively reduce both total cholesterol and triglycerides in patients with combined hyperlipidemia and familial hypercholesterolemia [8,36]. The present study has confirmed these observations and furthermore has shown that omega-3 fatty acids have an additive effect in lowering triglycerides, total cholesterol (borderline) and apoE when added to the statins.…”
Section: Discussionsupporting
confidence: 87%
“…19,26,27 Unfortunately, data on minor injuries were not available for our cohort to test this hypothesis. Furthermore, physical exercise of moderate and high intensity is associated with several immediate alterations in the hemostatic system, such as increased platelet reactivity, 28 shortened bleeding-time, 29 elevated plasma levels of factor VIII, 30 von Willebrand factor, 30,31 and fibrinogen, 32 increased plasma viscosity, 32 increased endogenous thrombin formation assessed by thrombin-antithrombin complex formation, 30 and transient increased fibrinolytic activity associated with increased plasma levels of tissue plasminogen activator 33 with subsequent inhibition of fibrinolytic activity monitored by prolongation of whole blood clot lysis time. These acute prothrombotic changes in the hemostatic system may contribute to the increased risk of acute coronary syndromes associated with physical exertion.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…15 The study was performed as a double-blind, placebocontrolled crossover trial. The study included three intervention periods of 6 weeks each interrupted by washout periods of 6 through 8 weeks.…”
Section: Experimental Designmentioning
confidence: 99%